Method for testing cutting damage depth of III-V family single crystal

Through multi-step corrosion and optimal corrosion testing methods, the technical gap in cutting damage depth detection of Group III-V single crystal materials was solved, and accurate detection of materials such as GaSb and InAs was achieved, testing accuracy and efficiency were improved, and the process was guided. Improvements and surface treatment.

CN119480669AActive Publication Date: 2025-02-18KUNMING INST OF PHYSICS
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202411594500.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-09
Publication Date
2025-02-18
Estimated Expiration
2044-11-09

AI Technical Summary

Technical Problem

The prior art lacks effective methods to detect the cutting damage depth of Group III-V single crystal materials, especially materials such as GaSb and InAs, which affect the performance of their optoelectronic devices.

Method used

Through a test method that includes multi-step corrosion and preferred corrosion, the corrosion time and area are controlled by a protective film, and the damage layer on the wafer surface is gradually revealed, and the depth of cutting damage is measured.

Benefits of technology

Accurate detection of the cutting damage depth of Group III-V single crystal materials is achieved, sub-damage defects can be detected, testing accuracy and efficiency are improved, and the improvement of cutting process and the quantification of surface treatment are guided.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure FT_1
    Figure FT_1
  • Figure FT_2
    Figure FT_2
  • Figure FT_3
    Figure FT_3
Patent Text Reader

Abstract

The invention provides a method for testing the cutting damage depth of III-V family single crystals, which is characterized by comprising the following steps: S1, cleaning the surface of a wafer, S2, measuring the initial thickness of the wafer, S3, pasting a protective film, S4, carrying out step-by-step corrosion to obtain a step table surface, S5, carrying out preferential corrosion liquid to enable the cutting damage to appear, S6, observing and testing the surface of the step of the wafer, and S7, testing the cutting damage depth of the III-V family single crystals. And obtaining the cutting damage depth of the III-V family single crystal. The method is high in test precision, can detect sub-damage defects which cannot be detected by an existing test method, is simple and time-saving in sample preparation and operation, and is high in test efficiency. By adopting the method disclosed by the invention, the damage caused by the cutting process of the III-V family single crystal can be quantitatively evaluated so as to guide the improvement of the cutting process, and meanwhile, quantitative guidance can be provided for the removal amount of the III-V family wafer surface treatment process.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention provides a testing method, in particular to a cutting damage depth testing method for III-V group single crystals, belonging to the technical field of semiconductor crystal material testing. Background Art

[0002] III-V compound crystal materials are an important branch in the field of semiconductor materials. Narrow bandgap materials such as gallium antimonide (GaSb) and indium arsenide (InAs) have the advantages of small effective electron mass, high electron mobility, and long carrier lifetime, so they are suitable for the preparation of high-performance optoelectronic devices, such as infrared detectors, lasers, and thermophotovoltaic cells. At the same time, the development of high-performance III-V semiconductor optoelectronic devices has put forward the demand for high-quality GaSb and InAs single crystal materials.

[0003] However, in the process of cutting and processing III-V group single crystal materials, it is inevitable to introduce cracks, dislocations, phase changes, amorphous layers and other damages on their surfaces. The quality of the surface of single crystal materials will directly affect the performance of the crystal and the quality of the epitaxial film. For example, the incompleteness of the surface lattice will affect the uniformity of the resistivity of the ion implantation layer; surface damage will increase the possibility of leakage; dislocation defects of the single crystal substrate will extend to the epitaxial film and reduce the carrier mobility. Therefore, the cut crystal needs to be ground, polished and other surface treatments to obtain a damage-free, low-roughness, clean single crystal surface. In order to accurately guide the removal amount of subsequent surface treatment processes to achieve efficient processing of crystal materials, it is very important to detect and analyze the thickness of the damaged layer on the crystal surface.

[0004] At present, surface damage depth detection methods have been developed for a variety of single crystal materials (such as silicon, silicon carbide, cadmium zinc telluride, and lithium niobate), but the cutting damage depth testing method for III-V group single crystals including GaSb and InAs is still blank. Summary of the invention

[0005] In order to solve the technical gap problem in the cutting damage depth testing method of III-V group single crystal materials, and at the same time, to further optimize the cutting process of III-V group single crystal materials such as gallium antimonide (GaSb) and indium arsenide (InAs) and provide quantitative guidance for the surface treatment of III-V group single crystal wafers, the present invention provides a cutting damage depth testing method for III-V group single crystal materials.

[0006] The present invention is accomplished by the following technical solutions: A method for testing the cutting damage depth of III-V group single crystal materials, characterized by comprising the following steps: S1, wafer surface cleaning: Take a (100) wafer cut from a III-V group single crystal material, rinse it with acetone three times and ethanol three times in sequence, and blow it dry with nitrogen for later use; S2, initial wafer thickness measurement: Use a thickness gauge to measure the thickness of the wafer at multiple points and record the data as: D1, D2, D3,…, D n , the purpose is to eliminate the impact of the thickness difference of the wafer itself on the test accuracy; S3, apply protective film: A whole protective film is attached to the back of the wafer to protect the back from corrosion during the whole experiment, and n strips of protective film with equal width and arranged in parallel are attached to the front of the wafer one by one to control the corrosion time of different positions of the wafer during the step-by-step corrosion process; S4, step-by-step etching to obtain a stepped terrace: The nth protective film on the front of the wafer is peeled off, and the wafer is immersed in a non-preferential etching solution for a soaking time of Δt, and then rinsed with ultrapure water after being taken out; then the n-1th protective film on the front of the wafer is peeled off, and the wafer is immersed in a non-preferential etching solution for a soaking time of Δt, and then rinsed with ultrapure water after being taken out; this is repeated until only one protective film is left on the front of the wafer; a stepped wafer table can be obtained by the above-mentioned distributed etching method; S5, select the best corrosive liquid to make the cutting damage visible: After peeling off the last protective film on the front of the wafer, soak the wafer in the selective etching solution for 3-5 minutes, take out the wafer and rinse it with a large amount of ultrapure water, and then blow it dry with nitrogen; S6, observe and test the wafer step surface: The thickness of the stepped wafer table was tested and the surface morphology was photographed using a non-contact measuring microscope. The final thickness of the crystal covered by the first to nth protective film was obtained as follows: d1, d2, d3,…, d n ; S7, obtain the cutting damage depth of III-V group single crystal: According to the surface morphology photos obtained by S6, the following phenomena can be observed: as the etching time increases, the thickness of the wafer decreases and the density of the etching pits also gradually decreases. However, when the density of the etching pits decreases to a certain extent, it will no longer change with the thinning of the wafer. At this time, the density of the etching pits is the density of dislocation defects inside the crystal, indicating that the cutting damage layer on the wafer surface has been completely removed. The minimum wafer thickness difference Δd corresponding to the minimum value of the etching pit density is i That is the cutting damage depth (Δd i =D i -d i ).

[0007] The III-V group single crystals include, but are not limited to, gallium antimonide (GaSb) and indium arsenide (InAs).

[0008] The single crystal cutting methods of S1 include but are not limited to multi-wire cutting and inner circle cutting.

[0009] The non-preferential etching solution of S4 includes but is not limited to: A mixture of bromine and methanol, with a bromine concentration of 1% to 5% by volume; Alternatively, a mixture of bromine + methanol + ethylene glycol, the volume ratio of the three being 1:6:18; Alternatively, a mixture of phosphoric acid and hydrogen peroxide, the volume ratio of the two is 1:1.

[0010] In the step-by-step etching of S4, the immersion time Δt is controlled within a range of 3 to 10 minutes. Due to the difference in total etching time at positions covered by different protective films, a stepped wafer table can be obtained.

[0011] The step-by-step etching of S4 can obtain a stepped wafer table without introducing new surface damage. Different table tops have different etching depths and thus fall on different areas of the wafer surface: damaged areas (including crack areas, amorphous areas, deformation areas, etc.) and non-damaged areas.

[0012] The preferred etching solution of S5 is as follows: For GaSb (100) wafers, the preferred etching solution is a mixture of hydrochloric acid + hydrogen peroxide + water, with the volume ratio of the three being 2:2:1; For InAs (100) wafers, the preferred etching solution is a mixture of hydrochloric acid and sulfuric acid, with the volume ratio of the two being 1:1.

[0013] The preferential etching solution used in S5 has a faster etching rate on crystal defects, so the defect state of the crystal surface can be evaluated by observing the size and density of the etching pits. Combined with the stepped wafer table obtained by the step-by-step etching method, damage defects at different depths on the wafer surface can be simultaneously displayed.

[0014] The thickness gauge, protective film, non-contact measuring microscope, etc. used in the present invention are all conventional equipment and commercially available products.

[0015] The present invention has the following advantages: ① High test accuracy, sub-damage defects can be detected, which cannot be detected by other existing test methods including double crystal diffraction half-peak width method, cross-section microscopy method, etc.; ② High test efficiency, simple sample preparation and operation, saving time. The present invention can quantitatively evaluate the damage caused by the cutting process of III-V group single crystals and guide the improvement of the cutting process. At the same time, it can provide quantitative guidance for the removal amount of the surface treatment process of III-V group wafers. BRIEF DESCRIPTION OF THE DRAWINGS

[0016] Figure 1 is a flow chart of the testing method of the present invention; Figure 2 Schematic diagram of the wafer structure obtained through steps S1-S5 of the present invention; Figure 3 The optical microscope photos of the surface of the GaSb single crystal slice of Example 1 of the present invention, wherein: (a) the step terrace morphology after step-by-step etching with a non-preferential etching solution; (b) the step terrace morphology after etching with a preferential etching solution; Figure 4 Surface optical microscope photographs of the InAs single crystal slice of Example 2 of the present invention, including: (a) the step terrace morphology after step-by-step etching with a non-preferential etching solution; (b) the step terrace morphology after etching with a preferential etching solution. DETAILED DESCRIPTION

[0017] The following will be combined with the embodiments of the present invention and the accompanying drawings to clearly and completely describe the technical solutions in the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention. Example

[0018] The present invention provides a method for testing the cutting damage depth of GaSb single crystal slices, comprising the following steps: S1, GaSb wafer surface cleaning: A (100) wafer obtained by inner circle cutting of a GaSb single crystal was taken, the feed rate of the inner circle cutting was 1.5 mm / h, and the wafer size was 40 mm×50 mm. The wafer was rinsed with acetone three times and ethanol three times in sequence, and then dried with nitrogen for later use; S2, GaSb wafer initial thickness measurement: The thickness of the GaSb (100) wafer was measured with a thickness gauge, and a point was measured every 10 mm along the long side, and the data were recorded: D1, D2, D3, D4, D5. The specific data are shown in Table 1. S3, apply protective film: A whole protective film was pasted on the back of the GaSb (100) wafer to protect the back from corrosion during the whole experiment. Five protective films were pasted on the front of the wafer in parallel with the short edge (each protective film was 15 mm wide and pressed 5 mm above the previous one) to control the corrosion time of different positions of the wafer during the step-by-step corrosion process. S4, step-by-step etching to obtain a stepped terrace: After peeling off the fifth protective film on the front side of the GaSb (100) wafer, the wafer was immersed in a mixture of bromine and methanol (the volume concentration of bromine was 3%) for 5 minutes, and then rinsed with ultrapure water. Then, the fourth protective film on the front side of the wafer was peeled off and the above operation was repeated until only one protective film was left on the front side of the wafer. Since the total etching time at different positions covered by the protective film was different, namely, t1=0, t2=5min, t3=10min, t4=15min, and t5=20min, a stepped wafer surface was obtained. S5, select the best corrosive liquid to make the cutting damage visible: Remove the last protective film on the front of the GaSb (100) wafer, soak the wafer in a mixture of hydrochloric acid + hydrogen peroxide + water (volume ratio of 2:2:1) for 3 minutes, then take it out, rinse it with a large amount of ultrapure water, and then blow it dry with nitrogen to obtain the following: Figure 2 The step-shaped GaSb wafer with defective etch pits shown is used to complete the sample preparation; S6, observe and test the wafer step surface: The thickness of the step surface of the GaSb wafer was measured and the surface morphology was photographed using a non-contact measurement microscope. Figure 3 ), the final thickness of the crystal covered by the 1st to 5th protective films are: d1, d2, d3, d4, d5, and the specific data are shown in Table 1; S7, obtain the cutting damage depth of GaSb single crystal: Observe the surface morphology of GaSb wafer obtained by S6 ( Figure 3 ), it can be seen that when the non-preferential etching time is 20min, the corrosion pits on the wafer surface basically disappear, and the wafer thickness difference corresponding to this position Δd5=45μm is the cutting damage depth of the GaSb single crystal.

[0019] Table 1

[0020] Based on the test method of Example 1 of the present invention, it is found that the thickness of the damaged layer introduced on the surface of the GaSb wafer by inner circle cutting at a feed rate of 1.5 mm / h is 45 μm, which means that the amount of removal of the subsequent surface treatment of the GaSb wafer must be no less than 45 μm. At the same time, the thickness of the damaged layer can be reduced by further reducing the feed rate, but the balance with the slicing efficiency should be considered. Example

[0021] The present invention provides a method for testing the cutting damage depth of an InAs single crystal slice, comprising the following steps: S1, InAs wafer surface cleaning: Take a (100) wafer obtained by inner circle cutting of an InAs single crystal, the feed speed of the inner circle cutting is 1.0 mm / h, the wafer size is 30 mm×40 mm, the wafer is rinsed with acetone three times and ethanol three times in sequence, and then blown dry with nitrogen for later use; S2, InAs wafer initial thickness measurement: The thickness of the InAs (100) wafer was measured with a thickness gauge, and a point was measured every 10 mm along the long side, and the data were recorded: D1, D2, D3, D4. The specific data are shown in Table 2. S3, apply protective film: A whole protective film was pasted on the back of the InAs (100) wafer to protect the back from corrosion during the whole experiment. Four protective films were pasted on the front of the wafer in parallel with the short edge (each protective film was 15 mm wide and pressed 5 mm above the previous one) to control the corrosion time of different positions of the wafer during the step-by-step corrosion process. S4, step-by-step etching to obtain a stepped terrace: After peeling off the fourth protective film on the front of the InAs (100) wafer, soak the wafer in a mixture of bromine and methanol (the volume concentration of bromine is 2%) for 10 minutes, take it out and rinse it with ultrapure water; then peel off the fourth protective film on the front of the wafer and repeat the above operation until only one protective film is left on the front of the wafer. Since the total etching time at different positions covered by the protective film is different, respectively: t1=0, t2=10min, t3=20min, t4=30min, a stepped wafer surface is obtained; S5, select the best corrosive liquid to make the cutting damage visible: Remove the last protective film on the front of the InAs (100) wafer, soak the wafer in a mixture of hydrochloric acid and sulfuric acid (volume ratio of 1:1) for 4 minutes, take it out, rinse it with a large amount of ultrapure water, and then blow it dry with nitrogen. Figure 2 The step-shaped InAs wafer with defective etch pits shown, completing the sample preparation; S6, observe and test the wafer step surface: The thickness of the step surface of the InAs wafer was measured and the surface morphology was photographed using a non-contact measurement microscope. Figure 4 ). The final thickness of the crystal covered by the 1st to 4th protective films are: d1, d2, d3, d4, and the specific data are shown in Table 2; S7, obtain the cutting damage depth of InAs single crystal: Observe the surface morphology of the InAs wafer obtained by S6 ( Figure 4 ), it can be seen that when the non-preferential etching time is 30min, the corrosion pits on the wafer surface basically disappear, and the wafer thickness difference corresponding to this position Δd4=27μm is the cutting damage depth of the InAs single crystal.

[0022] Table 2

[0023] Based on the test method of Example 2 of the present invention, it is found that the thickness of the damaged layer introduced on the surface of the InAs wafer by inner circle cutting at a feed rate of 1.0 mm / h is 27 μm, which means that the amount of removal of the subsequent surface treatment of the InAs wafer must be no less than 27 μm. At the same time, the thickness of the damaged layer can be reduced by further reducing the feed rate, but the balance with the slicing efficiency should be considered.

Claims

1. A method for testing the cutting damage depth of a III-V group single crystal, characterized in that The following steps are involved: S1, wafer surface cleaning: Take a (100) wafer cut from a III-V group single crystal material, rinse it with acetone three times and ethanol three times in sequence, and blow it dry with nitrogen for later use; S2, initial wafer thickness measurement: Use a thickness gauge to measure the thickness of the wafer in step S1 at multiple points and record the data as: D1, D2, D3,…, D n ; S3, apply protective film: In step S2, a whole protective film is pasted on the back of the wafer to protect the back from corrosion during the whole experiment, and n strips of protective film with equal width and arranged in parallel are pasted on the front of the wafer one by one; S4, step-by-step etching to obtain a stepped terrace: The nth protective film on the front side of the wafer in step S3 is uncovered, and the wafer is immersed in a non-preferential etching solution for a soaking time of Δt, and then rinsed with ultrapure water after being taken out; then the n-1th protective film on the front side of the wafer is uncovered, and the wafer is immersed in a non-preferential etching solution for a soaking time of Δt, and then rinsed with ultrapure water after being taken out; and this is repeated until only one protective film is left on the front side of the wafer; S5, select the best corrosive liquid to make the cutting damage visible: After removing the last protective film on the front side of the wafer in step S4, immerse the wafer in the selective etching solution for 3 to 5 minutes, take out the wafer and rinse it with a large amount of ultrapure water, and then blow dry it with nitrogen; S6, observe and test the wafer step surface: The thickness of the stepped wafer table in step S5 is tested and the surface morphology is photographed using a non-contact measuring microscope, and the final thickness of the crystal covered by the first to nth protective films is obtained as follows: d1, d2, d3,…, d n ; S7, obtain the cutting damage depth of III-V group single crystal: According to the surface morphology photos obtained in step S6, the following phenomena are observed: as the etching time increases, the thickness of the wafer decreases and the density of the etching pits also gradually decreases. However, when the density of the etching pits decreases to a certain extent, it will no longer change with the thinning of the wafer. The density of the etching pits at this time is the density of dislocation defects inside the crystal, indicating that the cutting damage layer on the wafer surface has been completely removed. The minimum wafer thickness difference Δd corresponding to the minimum value of the etching pit density is i That is the cutting damage depth (Δd i =D i -d i ).

2. A method for testing the cutting damage depth of a III-V group single crystal according to claim 1, characterized in that The III-V group single crystals include, but are not limited to, gallium antimonide (GaSb) and indium arsenide (InAs).

3. A method for testing the cutting damage depth of a III-V group single crystal according to claim 1, characterized in that The single crystal cutting methods of S1 include but are not limited to multi-wire cutting and inner circle cutting.

4. A method for testing the cutting damage depth of a III-V group single crystal according to claim 1, characterized in that The non-preferential etching solution of S4 includes but is not limited to: A mixture of bromine and methanol, with a bromine concentration of 1% to 5% by volume; Alternatively, a mixture of bromine + methanol + ethylene glycol, the volume ratio of the three being 1:6:18; Alternatively, a mixture of phosphoric acid and hydrogen peroxide, the volume ratio of the two is 1:

1.

5. A method for testing the cutting damage depth of a III-V group single crystal according to claim 1, characterized in that In the step-by-step corrosion of S4, the immersion time Δt is controlled within 3 to 10 minutes.

6. A method for testing the cutting damage depth of a III-V group single crystal according to claim 1, characterized in that The preferred etching solution of S5 is as follows: For GaSb (100) wafers, the preferred etching solution is a mixture of hydrochloric acid + hydrogen peroxide + water, with the volume ratio of the three being 2:2:1; For InAs (100) wafers, the preferred etching solution is a mixture of hydrochloric acid and sulfuric acid, with the volume ratio of the two being 1:1.

Citation Information

Patent Citations

  • Preparation method of sample for detecting sub-surface damage depth of ultra-thin silicon wafer

    CN104034568A

  • Method for measuring sub-surface affected layer depth and morphology of optical material

    CN104061853A

  • Method for detecting thickness of damaged layer in silicon single crystal processing

    CN117457519A

  • Structure for laying nanobeam on (111) crystal surafe silicon sheet and its making method

    CN1743261A

  • Nitride semiconductor substrate and nitride semiconductor device

    CN1933195A